IMPLEMENTASI GAYA PENYUTRADARAAN KOORDINATOR DALAM PROGRAM ACARA FEATURES JELAJAH NUSANTARA (EPISODE 1: “PUNTANG YANG TERKENANG” ) - Bawono, Muhammad Abdul Aziz Arief (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2023)
ABSTRACT This article discusses innovations in updating the narrative style of the feature documentary television program "Jelajah Nusantara" (Episode: Puntang Yang Terkenang). A combination of expository and interactive narrative styles, presented with a 3 in 1 concept in a coordinator directing style. The purpose of combining these two narrative styles is to ensure that the roles of the narrator and presenter, who usually stand alone, actively interact with each other, combined with the narrator providing information with visualized images as confirmation of the existing information. The 3 in 1 concept in each episode of this television program displays elements of recreation, education and sensation in one tourist attraction. The creation of this Documentary Features Event Program began with research using qualitative research methods, and creation methods with pre-production, production and post-production stages. As a result, the team was able to realize the event program concept by using a coordinator directing style which places the director/event director in the position of the person who coordinates the crew and talent involved to be able to realize the event program concept according to the event director's description. ABSTRAK Tulisan ini membahas tentang inovasi pembaharuan gaya penuturan program televisi features dokumenter dalam program acara “Jelajah Nusantara” (Episode: Puntang yang Terkenang). Penggabungan gaya penuturan ekspositori dan interaktif, disajikan dengan konsep 3 in 1 dalam gaya penyutradaraan koordinator. Penggabungan antara 2 gaya penuturan ini bertujuan agar peran narator dan presenter yang biasanya berdiri sendiri-sendiri, menjadi aktif berinteraksi satu sama lain dipadukan dengan narator yang memberikan informasi dengan visualisasi gambar sebagai penegas dari informasi yang ada. Konsep 3 in 1 dalam setiap episode program televisi ini menampilkan unsur Rekreasi, Edukasi dan Sensasi dalam satu tempat wisata. Penciptaan Program Acara Features Dokumenter ini dimulai dengan riset yang menggunakan metode penelitian kualitatif dan metode penciptaan dengan tahapan pra produksi, produksi dan pasca produksi. Hasilnya team dapat mewujudkan konsep program acara dengan menggunakan gaya penyutradaraan koordinator yang menempatkan posisi sutradara/pengarah acara sebagai orang yang mengkordinir crew dan talent yang terlibat untuk dapat merealisasikan konsep program acara sesuai gambaran pengarah acara.